Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

Adverse childhood experiences, adult adiposity, and risk of young-onset breast cancer subtypes in a population-based case-control study - Lydia Marcus Post; Young Ik Cho; James Topitzes; DPhuong Do; Dorothy R. Pathak; Ann S. Hamilton; Amani M. Nuru-Jeter; Kelly A. Hirko; Jamila L. Kwarteng; Richard Houang; Ann G. Schwartz; Ellen M. Velie (Cancer Causes & Control, 2026)
Purpose Adverse childhood experiences (ACEs) are hypothesized to increase breast cancer risk via social and physiological pathways, yet associations between ACEs and young-onset breast cancer (BC) subtypes–and potential mediators (e.g., adiposity) of these associations–are largely unstudied. We sought to evaluate associations between ACEs and young-onset BC molecular subtypes, and the potential mediating effects of adiposity, in a population-based case–control study of invasive young-onset BC. Methods Cases (n = 1,754) were identified from the Los Angeles County and Metropolitan Detroit SEER registries, 2010–2015, and area-based, frequency-matched controls (n = 1,350) sampled from the 2010 Census. Associations between ACEs aged < 18 years and young-onset BC (diagnosed ages 20 to < 50 years), overall and by subtype (luminal A, luminal B, HER2 + , triple negative [TN]), were examined using weighted logistic regression. Adult adiposity (i.e., body mass index 12 months before diagnosis, waist circumference at interview) was evaluated as a mediator of these associations using weighted path analyses. Results ACEs (≥ 1 vs 0) were not significantly associated with young-onset BC (all p trend > 0.10); however, reporting one ACE (vs 0) was associated with TN (odds ratio [OR] = 1.85 [95% confidence interval [95%CI] = 1.08–3.16]). For individual ACEs, death of a loved one (vs 0 ACEs) was associated with HER2 + (OR = 2.50 [95%CI = 1.06–5.88]) and potentially TN (OR = 1.72 [95%CI = 0.96–3.10]) young-onset BC; other associations were non-significant. In path analyses, ACEs had a significant total effect on luminal A (β = 0.08, p = 0.03) and TN (β = 0.13, p < 0.01) tumors, with adiposity mitigating this association for luminal A tumors (β = -0.01, p = 0.04; TN β = 0.00, p > 0.05). Conclusions Bereavement during childhood was associated with higher odds of HER2 + young-onset BC, and there was some evidence of an association between ACEs and other young-onset BC subtypes, particularly TN.

Large‐Scale Variation in Biodiversity–Ecosystem Functioning ( BEF ) Relationships in Aquatic Metacommunities on Terrestrial Islands - Joren M. Snoeks; Aranya Pathak‐Broome; James G. Hagan; Bram Vanschoenwinkel (Global Ecology and Biogeography, 2025)
Aim Recent work has shown that the biodiversity of potential colonists in a landscape (the local species pool) may be more important for ecosystem functioning than the biodiversity in local habitat patches. However, it is unknown how such biodiversity–ecosystem functioning (BEF) relationships may change across different biomes. To explore such patterns, nested insular ecosystems where variation in local biodiversity and local species pool biodiversity can be reliably quantified can provide important insights. Location Rock pool metacommunities on isolated rocky outcrops (i.e., inselbergs) in Africa, Australia, Europe, and North America. Time Period Sampling: 2011–2019. Major Taxa Studied Freshwater invertebrates. Methods We assembled a large‐scale dataset of invertebrate metacommunities from replicated rock pool clusters on inselbergs as a model system to test the ability of local biodiversity and local species pool biodiversity to explain community biomass in organisms with different survival strategies (active or passive dispersers). To test our hypotheses, we used a combination of directed acrylic graph‐based path analyses and general linear mixed‐effects models. Results The biodiversity of the local species pool was influenced by climate but did not significantly impact community biomass. Instead, local environmental gradients seem to override any species pool effects on community biomass. However, in line with expectations, the relationship between local biodiversity and biomass varied across inselbergs. Contrary to expectations, inselberg prominence did not influence the BEF slope. However, in drier conditions, the BEF relationship weakened for active dispersers, likely reflecting environmental limits on recolonisation. Thus, climate and dispersal strategy jointly shaped how biodiversity influenced community biomass. Main Conclusion This study illustrates that even in a simple ecosystem there can be substantial geographical variation in the relationship between biodiversity and ecosystem functioning that may be partially explained by environmental conditions and by the survival strategy of the organisms considered.

Measurement of the decay Ξ 0 → Λ γ with entangled Ξ 0 Ξ ¯ 0 pairs - M. Ablikim; M.N. Achasov; P. Adlarson; O. Afedulidis; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; I. Balossino; Y. Ban; et al. (Science Bulletin, 2025)

Exploring the toxicity of chromium on aquatic ecosystems: a comprehensive assessment of growth, physiological responses, genotoxicity, and histological alterations in Etroplus suratensis (Bloch, 1790) juveniles - Ramya V.; Madhuri S. Pathak; Kapil Sukhdhane; Kishore Kumar Krishnani; Thongam Ibemcha Chanu; Harini G.; Harshavarthini M. (Aquaculture International, 2024)

Development and validation of transient Thermal-Hydraulic model for SFR steam generators - G. Vikram; K. Natesan; M. Rajendrakumar; S.P. Pathak (Annals of Nuclear Energy, 2023)

Complete nucleotide sequence of the envelope gene of pseudocowpox virus isolates from Indian dromedaries (Camelus dromedarius) - G. Nagarajan; S. K. Ghorui; Sanjay Kumar; K. M. L. Pathak (Archives of Virology, 2010)

Isolation and characterization of Indian isolates of camel pox virus - V. Bhanuprakash; V. Balamurugan; M. Hosamani; G. Venkatesan; Bina Chauhan; V. A. Srinivasan; R. S. Chauhan; K. M. L. Pathak; Raj Kumar Singh (Tropical Animal Health and Production, 2010)

Poster abstracts - J. Ferrie; M. Shipley; F. Cappuccio; E. Brunner; M. Miller; M. Kumari; M. Marmot; A. Coenen; J. L. Castillo; F. Araya; G. Bustamante; L. Montecino; et al. (Sleep and Biological Rhythms, 2007)

Experimental biofilm and its application in malathion degradation - B. Kumari; A. Guha; M. G. Pathak; T. C. Bora; M. K. Roy (Folia Microbiologica, 1998)

The Imperata grasslands of tropical Asia: area, distribution, and typology - D. P. Garrity; M. Soekardi; M. van Noordwijk; R. de la Cruz; P. S. Pathak; H. P. M. Gunasena; N. van So; G. Huijun; N. M. Majid (Agroforestry Systems, 1996)